Answer:
(3,5)
Explanation:
For this equation, you need to solve it like simultaneous equations. Both of these have a 4y, so that is relatively easy to do, once you know how to.
The signs in front of the 4y are different, so you add the 2 equations (to remove the ys all together).
This should be (2x+-8x)+(-4y+4y)=(-14+-4), or (2x-8x)+(4y-4y)=(-14-4).
This can be expanded to -6x+0=-18, or -6x=-18.
Dividing both sides by -6 leaves you with x=3.
To find y, substitute this x value into either equation (I picked equation 1 as it is simpler). This gives you 2(3)-4y=-14, expanded to 6-4y=-14.
From there, you subtract the 6 from both sides, to get the y alone (giving -4y=-20).
By dividing both sides by -4, you get y=5.
This means the answer is (3,5).
**This question involves simultaneous equations, so you might want to look at that. I'm always happy to help!